The delicious history of the holiday - Inglis, Fred, 1937- (Routledge, 2000)
Fred Inglis traces the rise of the holiday from its early roots in the Grand Tour, through the coming of Thomas Cook and his Blackpool packages, to sex tourism and the hippie trail to Kathmandu.